Vocational High School Teachers Continuous Professional Learning - Dewi Hasanah; Samsudi Samsudi; Muhammad Khafid; Amir Mahmud (Universitas Negeri Semarang, 2023)
The quality of vocational teachers is one of the main challenges affecting the quality of vocational education graduates. This paper discusses strategies that can be applied in continuing professional learning for vocational teachers at SMK, this qualitative research uses a phenomenological approach related to continuous professional learning carried out by SMK teachers, data obtained by conducting interviews followed by reviewing various literature. Strategies that can be implemented in continuous professional learning for vocational teachers can be carried out holistically including self-development activities, publications and innovative work in the form of training, in-house training, MOOC or vocational productive teacher competency certification tests carried out by teachers individually and collectively through MGMP. School; by facilitating teachers to participate in product-based training. System; by improving the content of teacher professionalism improvement activities at schools, education offices, universities, teachers' unions or professional associations. In addition, in the implementation of teacher professional learning strategies, it is necessary to pay attention to five dimensions, namely motivation, access, provision, content and quality. The implementation of this strategy is expected to have a positive impact on improving the quality of learning carried out by teachers besides that it can improve the quality of learning and improve teacher well-being.